BIOPROSPECTING NEGLECTED BOTANICALS AS PHYTO-FERTILIZER FOR UNDERUTILIZED FOOD CROPS - Abiala, Moses Akindele (Journal of Agricultural Sciences (Belgrade), 2019)
Botanicals are part of the bioresources for sustainable growth of food crops, however some botanicals have been neglected. This study investigates the potential effects of neglected botanicals on selected underutilized food crops (millet, sorghum and sesame) in Nigeria. Blotter technique and soil inoculation methods were used to evaluate the best botanicals that could be employed to enhance seed germination (SG) and seedling growth of underutilized food crops. With the exception of Newbouldia laevis, other botanicals enhanced seed germination of all tested crops. Ficus asperifolia and Parquetina nigrescens significantly (p<0.05) enhanced the radicle length (RL) while the plumule length (PL) remains unaffected. Specifically, observation shows that Newbouldia laevis completely inhibited sesame seed germination and seedling growth while Parquetina nigrescens enhanced millet height and sesame number of leaves. Generally, the effect of the botanicals on each crop was specific. Thus, these neglected botanicals stand the chance to enhance and sustain seedlings of underutilized food crops in Nigeria. Further study would be carried out to uncover the chemical components in the tested botanicals.